Analysis of the Zeolite Size Effect on the Content of Chemical Compounds in Acid Activated Natural Zeolite - Fadliah Fadliah; Reno Pratiwi; Wiwik Dahani; Riskaviana Kurniawati; Kartika Fajarwati Hartono; Dina Asmaul Chusniyah; Lailatul Wastiyah; Hadi Purnomo (Penerbitan Universitas Trisakti, 2021)
One of the zeolite producing areas in Indonesia is Sukabumi. Natural zeolite originating from Sukabumi is composed of three main types of minerals: mordenite, clinoptilolite, and quartz. Zeolite as a catalyst can be improved by carrying out physical and chemical activation processes. Physically the catalyst can be activated by reducing the size of the zeolite through the grinding and sieving method. This physical activation process can increase the surface area of the zeolite. In this study, variations in the size of zeolite 80 mesh and 100 mesh were carried out that chemically activated by the acid activation method through immersion of natural zeolite with HCl and HF from this acid activation process it will increase the acidity of the zeolite. Measurement of functional groups and chemical compounds in activated zeolite using XRF and FTIR. The results of XRF analysis showed that the SiO2 content in 80 mesh zeolite was 69.5% and in 100 mesh zeolite was 82.1% and the FTIR analysis showed the presence of the C-H alkene functional group at a wavelength of 675-995 cm-1, ring C-H aromatic at a wavelength of 690-900 cm-1, C-O alcohol/ether/carboxylic acid/ester at wavelength 1610-1680 cm-1, functional group C=C alkene 1610-1680 cm-1, the O-H functional group is carboxylic acid at a wavelength of 3500-3650 cm-1 and an alcohol monomer/phenol O-H functional group at a wavelength of 3590-3650 cm-1.